Exploring Cognitive and Gender Factors in Mathematical Creativity: Evidence from Indonesian Vocational Schools - Pantaleon, Kristianus Viktor; Pereira, Jerito; wijaya, Tommy Tanu; Visera, Elisabeth (Universitas Muhammadiyah Mataram, 2025)
Despite the increasing focus on creativity in mathematics education, research on the combined effects of cognitive style and gender on mathematical creative thinking in vocational high schools is still scarce, especially in Indonesia. This study investigated the influence of cognitive style and gender on the mathematics creative thinking of 60 eleventh-grade students in a vocational high school, classified as Field Independent (FI) or Field Dependent (FD) by the Group Embedded Figures Test (GEFT). Mathematical creativity, which includes fluency, flexibility, and originality, was assessed using an open-ended test that was verified by two experts in mathematics education and pilot-tested for reliability. Data were examined via two-way ANOVA. The findings indicated that FI students markedly surpassed their FD counterparts across genders (p < 0.001), although gender disparities were not statistically significant, although females exhibited a tendency for enhanced fluency and inventiveness, while males shown better flexibility. No notable interaction between cognitive style and gender was detected. These findings underscore the superiority of cognitive style over gender in influencing mathematical creativity in vocational environments and present the inaugural empirical evidence for this combination effect within the Indonesian context. They propose that vocational mathematics instruction must be cognitively adaptive providing structured scaffolding and collaborative methods for FD learners, and open-ended, self-directed tasks for FI learners to enhance creativity and problem-solving abilities pertinent to real-world vocational challenges.